Student's Learning Activities At Vinh Long University Of Technology Education (Journal of Namibian Studies : History Politics Culture, 2023)
Students' self-study activities have great significance for students' learning outcomes. This article presents the results of research on the current status of self-study skills of students at Vinh Long University of Technology Education. They include self-study planning skills, reading and document research skills, classroom self-study skills (directly studying with lecturers), self-studying skills at home (learning indirectly with lecturers), and skills in testing and evaluating students' self-study results. The research results aim to help students self-direct, self-adjust their self-study methods, and at the same time it gives advice to lecturers on how to foster self-study capacity for students to study more effectively.